The Circadian Clock as an Essential Molecular Link Between Host Physiology and Microorganisms - Murakami, Mari; Tognini, Paola (Frontiers in Cellular and Infection Microbiology, 2020)
Advances in high-throughput sequencing technologies in the past decade has led to a tremendous growth in knowledge about the role played by microorganisms on our body health. Trillions of microbes live in close symbiosis with their host, and have impacts on various aspects of host physiology as well as predisposition to disease. This is a consequence of the direct interaction between host cells and microbes or their signaling molecules, such as metabolites, which can reach and exert their effects in distal tissues. Among the essential factors modulating the human body's ecosystem of symbionts, the circadian clock might be one of the key regulators. The endogenous clock is a highly conserved timekeeper able to align organismal physiology to the daily cycle, thus maximizing survival and fitness. Circadian rhythms coordinate whole-body biological processes synchronizing cellular biochemical reactions, tissue function and finally controlling systemic homeostasis. Intriguingly, growing body of evidence has demonstrated that the host circadian cycle governs the structure of the gut microbiota community and its diurnal rhythmicity, whereas the microbes contribute to maintenance of clock function. In this review, we will give an overview of the multisystem aspects of microbiome-host interactions in the context of circadian rhythmicity. In particular, the effect of the interaction clock-microbial communities on immune system function and metabolic homeostasis will be discussed. Finally, the possible implication of daily rhythm on the gut-microbiome-brain axis will be analyzed, focusing on the reciprocal effects of clock disruption and microbiota alterations on brain function and behavior.